Design of cold-formed steel structures. Eurocode 3: design of steel structures /: Eurocode 3: design of steel structures. Design of cold-formed steel structures. Part 1-3 (2013) - Dubina, Dan; Landolfo, R (Raffaele); Ungureanu, Viorel
No abstract available